Analysis of Arabic Language Textbooks Published by Quadra in 2022 for Class XI of Islamic High School Based on Common European Framework of Reference for Languages - Fitriasari, Rizqi Nur; Nurhidayati; Alfan, Muhammad; Maknuna, Salma Lulu; Ibrahim, Abdelrahman (Mantiqu Tayr: Journal of Arabic Language, 2025)
Textbooks play a crucial role in the Arabic language learning journey for non-Arabic-speaking students at the Madrasah Aliyah level. A well-structured textbook can act as a teaching aid and a roadmap for mastering language competencies that align with both national and international standards, such as the Common European Framework of Reference for Languages. One such textbook is “اللغة العربية 2” published by Quadra in 2022 for Year 11 students. However, research on this textbook remains limited. This study aims to examine the alignment of the textbook's content with established standards while investigating indicators of speaking skill competence based on the Common European Framework of Reference for Languages. Using a descriptive qualitative approach and content analysis methods, the primary data source is “اللغة العربية 2” supplemented by relevant literature. The findings indicate that the textbook meets standards for linguistic accuracy, material presentation, and visual layout. The speaking competencies are aligned with levels A2 and B1 of the Common European Framework of Reference for Languages. Topics like shopping and health correspond to level A2, promoting direct communication, while travel and technology fit level B1, encouraging extended speech and structured expression of experiences and opinions. Future research should explore other language skills within the same textbook for a comprehensive evaluation.